Chapter Neomodernist trends in Russian and Ukrainian poetry of the second half of the 20th century: theoretical problems and the European context - Achilli, Alessandro (Biblioteca di Studi Slavistici, 2019)
This article considers the presence of modernist elements in poetry from the second half of the 20th century, focusing in particular on Russian and Ukrainian examples. We argue for the necessity of properly recognizing and analyzing modernist phenomena in a period (1960s-1980s) when these have often been eclipsed by a tendency in literary criticism to overstate the role of Postmodernism. We also examine differences in the Western and Soviet cultural contexts and in the roles that Neomodernist poetics played in the poetry of various authors, groups and texts.